PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERMAIN JAWABAN PADA PEMBELAJARAN IPA FISIKA DI KELAS VII SMPN 34 PEKANBARU UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Hasanah, Ria Chuswatun; Nasir, Muhammad; ', Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aimed to describe and find out the improvement of the students motivation learning with implementation playing answers cooperative learning model. This type of research is a quasi-experimental, with non-equivalent control group design. The subject of this research are students class VII at SMPN 34 Pekanbaru, total of 72 students as divide into two group, experimental group and control group. The data in this research is a score of leraning motivation pree and post of treatment by implementation of playing answers cooperative learning model, analysis of the data uses descriptive and inferential analysis. Then, reference to the improvement of the students learning motivation by normalized gain (gain-N). The result of this research, score motivation of students at experimental class in high category and increase in the middle category with N-Gain 0,3, and the control class in the low category with N-Gain 0,1. While the results of inferential analysis showed a significant difference in motivation learning between experimental class and control class. Therefore, it can be concluded that the implementation of cooperative learning model playing answers able to improve the motivation in physics science study of students at class VII SMPN 34 Pekanbaru.Key Words: Cooperative Learning, Playing Answers, Motivation.